2012
DOI: 10.1155/2012/274305
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Drain Potential of Students in the African Health and Nonhealth Sectors

Abstract: The departure of health professionals to Europe and North America is placing an intolerable burden on public health systems in many African countries. Various retention, recall, and replacement policies to ameliorate the impact of this brain drain have been suggested, none of which have been particularly successful to date. The key question for the future is whether the brain drain of health sector skills is likely to continue and whether the investment of African countries in training health professionals wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This study revealed that high emigration potential was more likely for respondents younger than 25 years. Expectations about the future also influence migration and promote brain drain (Crush and Pendleton, 2012). This study showed overall low future expectation score is in line with an existing study of students in health and non-health sectors in southern African countries (Crush and…”
Section: Amorha Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…This study revealed that high emigration potential was more likely for respondents younger than 25 years. Expectations about the future also influence migration and promote brain drain (Crush and Pendleton, 2012). This study showed overall low future expectation score is in line with an existing study of students in health and non-health sectors in southern African countries (Crush and…”
Section: Amorha Et Alsupporting
confidence: 89%
“…Pendleton, 2012). Evidence indicates that negative perception towards the future, by students in the health professions, including pharmacy, is associated with the intention to migrate, for the long term (Crush and Pendleton, 2012), while a positive future expectation is linked to short term emigration and intention to remain or return to the country of origin (Owusu-Daaku et al, 2008;Wuliji et al, 2009). The overall low future expectation reported in this study is also in tandem with an existing study of pharmacy students in Ghana in which only a few respondents expressed optimism regarding possible future opportunities while others perceived pharmacy as being routine and lacking in challenges and prospects of making a real contribution to patient care (Owusu-Daaku et al, 2008).…”
Section: Amorha Et Almentioning
confidence: 99%
“…Although research has most often focussed on particular countries’ loss of professionals (e.g. Chikanda, 2005a; Crush and Pendleton, 2012) and others have noted the significant differences between African countries (e.g. Niger compared to Ghana; Clemens and Pettersson, 2008), the emigration of skilled health-care workers has nonetheless come to be talked about as a highly pressing sub-Saharan African public health problem.…”
Section: Problematizing Medical Migrationmentioning
confidence: 99%
“…The sample size is calculated and determined using the formula. 16 where: n = the minimum sample size…”
Section: Sample Size Determinationmentioning
confidence: 99%